1978
DOI: 10.1111/j.1365-2265.1978.tb01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone, Oestrogen, and Glucocorticoid Effects on Two Different Pituitary Glycoprotein Hormone Alpha Subunit Pools

Abstract: Seven hypothyroid women (six postmenopausal and one premenopausal) were treated with 200 or 300 pg of levo-T4 daily in order to suppress the secretion of TSH and its alpha and beta subunits. After such therapy, serum TSH and beta subunit of TSH (TSH-0) levels were usually not detectable. Serum alpha decreased from a mean value of 4.5 f 0.8 ng/ml to 2.8 f 0.4 ng/ml (P< 0.01). Serum LH and FSH levels were unchanged. Oestrogen administration (20 mg diethylstilboestrol daily for 3 or 5 days) to these patients furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It has been postulated that the normal pituitary gland contains two functionally different pools of a-subunit, one synthesized by thyrotroph cells and the other by gonadotroph cells (Kourides et al 1978). In this study we found that iv TRH and LRH caused increases of serum a-subunit in con¬ trols.…”
Section: Discussionmentioning
confidence: 75%
“…It has been postulated that the normal pituitary gland contains two functionally different pools of a-subunit, one synthesized by thyrotroph cells and the other by gonadotroph cells (Kourides et al 1978). In this study we found that iv TRH and LRH caused increases of serum a-subunit in con¬ trols.…”
Section: Discussionmentioning
confidence: 75%
“…It is likely that the secretion of FAS by thyrotroph cells of our patients is lower than that of controls, and this dissocia tion from the behavior of TSH is in favor of pituitary damage. It is well known that FAS is not only secreted by the gonadotroph but also by the thyrotroph cells [3], In fact there is experimental evidence that FAS secretion in normal subjects is not completely under GnRH control [4] and that administration of a GnRH antagonist has only a partial suppressive effect on FAS levels [7], The poor response of FAS, both to LH-RH and to TRH stimu lation, indicates that the pituitary damage in the course of the disease concerns not only the gonadotroph but also the thyrotroph cells which are both sensitive to iron overload. It is interesting to note that the patients who responded better to LH-RH stimulation, also responded better to TRH stimulation and a significant correlation existed 216 Tato/Lahlou/Zamboni/De Sanctis/De Luca/ Free Alpha-Subunits in Beta-Thalassemia Arrigo/Antoniazzi/Roger between the response of FAS to LH-RH and TRH in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the pituitary gland there are two separate a-subunit pools stimulated by hypotha lamic peptides: one arising from gonadotroph and stimu lated by LH-releasing hormone (LH-RH) and one from thyrotroph stimulated by thyrotropin-releasing hormone (TRH) [3]. The a-subunit is secreted by the anterior pitu itary also in a free form (FAS) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The a-subunit is secreted in a pulsatile manner by the thyrotropes and by the gonadotropes (6), but especially by the latter (7). Its production is stimulated by TRH (7) and by GnRH (8) and is suppressed with the use of thyroid hormone (9) or estradiol (1,10) in the absence of nonfunctioning tumors. Regulation by GnRH is the most important one, with 90% concordance between the pulses of the a-subunit and of LH (11).…”
Section: Introductionmentioning
confidence: 99%
“…The a-subunit of glycoprotein hormones, usually detected in the serum of normal individuals (1)(2)(3), has been used as a tumor marker for gonadotropin-or TSH-secreting pituitary adenomas (4), for GH-secreting tumors (4,5) and for nonsecreting pituitary tumors (3,4). The a-subunit is secreted in a pulsatile manner by the thyrotropes and by the gonadotropes (6), but especially by the latter (7).…”
Section: Introductionmentioning
confidence: 99%